2022
DOI: 10.13057/biodiv/d231011885
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and phylogenetic relationships of Begonia multangula based on atpB-rbcL non-coding spacer of cpDNA sequences

Abstract: Abstract. Warseno T, Efendi M, Chasani AR, Daryono BS. 2022. Genetic variability and phylogenetic relationships of Begonia multangula based on atpB-rbcL non-coding spacer of cpDNA sequences. Biodiversitas 23: 5491-5501. Begonia (Begoniaceae) belongs to Section Platycentrum-Sphenanthera Group which has a wide distribution from Sumatra to the Lesser Sunda Islands and Sulawesi. Information on B. multangula genetic variability and intraspecies relationships based on molecular characters is critical for developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…However, this site has no mutation in the nucleotide bases. Less genetic diversity was noticeable by having more conserved sites in the sequence (Warseno et al, 2022). Liu and Schardl (1994) reported that the high level of conservation of ITS sequences seemed involved with its function in processing rRNA…”
Section: Profile Of Its Sequence In C Pentandramentioning
confidence: 99%
“…However, this site has no mutation in the nucleotide bases. Less genetic diversity was noticeable by having more conserved sites in the sequence (Warseno et al, 2022). Liu and Schardl (1994) reported that the high level of conservation of ITS sequences seemed involved with its function in processing rRNA…”
Section: Profile Of Its Sequence In C Pentandramentioning
confidence: 99%